Efficacy of early versus late postpartum DIPSI test in gestational diabetes mellitus women for follow up - A., Geethalakshmi; S., Saraswathi; K., Kalaivani; C., Anjalakshi; Jain, Rajesh; V., Seshiah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The present study aimed to evaluate if postpartum gestational diabetes mellitus (GDM) screening can be performed during immediate post-delivery 72 hrs instead of six weeks postpartum for follow-up. Methods: Total 150 GDM patients were included. The sample size was calculated as 150 with Nimaster2.0 software. GDM patients are enrolled after meeting the exclusion criteria for the study. The GDM diagnosis was made by DIPSI test and treated as per guidelines. After delivery, the Dipsi test was done on PND-3 (PP1). Furthermore, all were kept on LSM irrespective of the glycaemic level DIPSI test was repeated in all Patients after 45 days (PP2). Results: All 150 patients had a DIPSI test on 3rd day post-partum (PP1) and repeat test at 45 days (PP2)., Of these, 60 patients (40%) showed negative DIPSI test on P1 and all remained in Group 1, with 63 patients having negative DIPSI test on PP2. 50 patients (33.3%) had blood glucose between 140-199 mg (Group 2) on PP1 and increased to 53 patients in PP2 in 45 days. 40 patients had diabetic (26.6%) value (Group 3) in PP1, and out of them 34 (22.6%) remained in group 3 in PP2 after 45 days post-partum. Conclusions: This pilot study shows that nearly 60% of the GDM patient have either IGT or diabetic value following delivery on 3rd day of PP1 and almost similar results in PP2. Hence, we can do the postpartum screening on the postpartum 3rd day and need not wait for 6 wks when more than 50% is lost for follow-up. This study shows among GDM 60% of them have underlying beta cell dysfunction.